Gestational age‐specific scoring systems for the prediction of coarctation of the aorta. (31st July 2014) - Gómez‐Montes, Enery; Herraiz, Ignacio; Gómez‐Arriaga, Paula Isabel; Escribano, David; Mendoza, Alberto; Galindo, Alberto
ABSTRACT Objectives To determine which combination of cardiac parameters provides the best prenatal prediction of coarctation of aorta (CoAo). Methods We selected all cases of simple cardiac asymmetry prenatally diagnosed in 2003–2013. Logistic regression was used to select the best predictors of CoAo. Results The study population included 115 fetuses. CoAo was confirmed in 52 neonates (45%). The sample was divided in two groups according to the gestational age (GA) at diagnosis: early group (EG) ≤28 weeks (n = 57), and late group (LG) >28 weeks (n = 58). CoAo was confirmed in 75% and 16% of cases, respectively. GA‐specific scoring systems with maximum two parameters were made, and the pairwise combination with the best diagnostic performance for each group was selected. In EG, the z‐score of ascending aorta (AAo) and aortic isthmus (three vessels and trachea view) showed the best diagnostic accuracy [area under receiver‐operating curve (AUC) 0.98, 95% confidence interval (CI) 0.94–1.00]. In the LG, the best results were provided by the tricuspid valve/mitral valve ratio with the main pulmonary artery/AAo ratio (AUC 0.84, 95% CI 0.67–1.00). Conclusions Gestational age‐specific scoring systems combining size‐based cardiac parameters may improve the accuracy of fetal echocardiography to stratify the risk of CoAo. The objectivity and simplicity of its components may facilitate its implementation in fetal cardiology units. © 2014 John Wiley & Sons, Ltd.